Linguistic ecology and its features in media: TV channel examples - Kuanyshbek Kenzhalin, Saltanat Shokabayeva, Aisha Zhumagulova, Gulbarshyn Syzdykova, Gulgaisha Sagidolda, (Opción, 2020)
The paper considers linguistic ecology and its features in media. It identifies the linguistic and societal issues using examples from Kazakh television. Linguistic ecology may be monitored in the Kazakh-language programs. As a result, media transfers ideological, emotional and even ultimate hopes of the audience. The paper gives some examples. The authors analyze the data and conclude that negative information, negative evaluation words prevail in the media.